The ecological life history of the Cape Bulbul - Liversidge, Richard (Department of Biological Sciences, 2016)
The study of the ecological life history of the Cape Bulbul Pycnonotus capensis was carried out in 20 hectares of coastal dune forest near Port Elizabeth, South Africa. Results from four years 1959 to 1962 are given in detail and only the number of breeding pairs present in 1958 have been used from observations that year. The Cape Bulbul is one of three closely related species of a predominantly tropical family. Intra specific breeding is rare and occurs only where man has altered the habitat. Distribution has altered slightly in 150 years where colonisation has occurred. Several conditions may influence distribution, the species is mainly limited to within winter or all year round zones of rainfall. Population of breeding pairs varies from nine to 19 pairs. It is the commonest species in the area. There is a 25% annual adult mortality with life expectancy of an adult about three years. Competition for food is negligible. Predators concern mainly the nesting cycle. Clutch size which is two or three is not regulated by food supply or population changes. Main changes are due to emigration and immigration which is apparently influenced by density-independent factors.